SYSTEMATIC DISINFORMATION: THE SPREAD OF MISLEADING INFORMATION AS A COLLECTIVE DYNAMIC ON TWITTER - Soares, Felipe Bonow (Brazilian Creative Industries Journal, 2022)
Disinformation is a worldwide problem and has been a key scholarship in the last few years. This paper contributes to the ongoing discussion on how disinformation spread on social media. This study uses a mixed-methods approach (Social Network Analysis, Connected Concept Analysis and Content Analysis) to analyze four political discussions on Twitter. The results show a structure of asymmetric polarization, in which one group (that supported Bolsonaro in the 2018 Brazilian elections) is strongly associated with disinformation spread. In addition, this study identifies a collective dynamic in disinformation spread as the volume of disinformation floats similarly for different levels of users depending on the context of the discussion analyzed. Based on these results, the idea of “systematic disinformation” is discussed.